Da'wah Through Instagram Among Female Muslims Celebrities In Malaysia - Adlene Aris; Fauziah Hassan (Universiti Sains Islam Malaysia, 2024)
The advancement of the Internet has made many social media networks emerge such as Facebook, Twitter, Instagram, YouTube, personal blogs and etc. with a variety of functions that also gloriously allocates space for da’wah activities and messages. This study examined how two Muslim female celebrities in Malaysia; Abby Abadi and Raisyyah Rania Yeap propagate da’wah messages through their Instagram by uploading pictures and videos they have shared during the first week of Ma’al Hijrah. A total of 5908 of pictures and videos were studied with Abby Abadi representing 5037 pictures/videos and Raisya Rania representing 871 pictures/videos. These two Muslim female celebrities were selected because they are seen as new trendsetters to Muslimahs with their new appearance, new look and their eagerness to spread Islamic messages through their Instagram actively. The researchers also discovered that both Abby Abadi and Raisyyah Rania Yeap received positive comments related to hijrah in terms of covering the aurah and also neutral comments related to online business. The researchers can conclude that both celebrities have their own strength and weaknesses but are very keen in spreading da’wah and have their own strong fan base of followers in Instagram. Therefore, a preliminary conclusion can be made that social media, especially Instagram can be used as a platform for da’ies to spread da’wah and well-meaning messages.